Composition and application thereof

By using cement, red mud, calcium sulfate waste residue powder and admixture compositions in soft soil curing and shield tunnel synchronous grouting, the shortcomings of existing materials in early strength, curing time, strength and salt corrosion resistance are solved, and efficient soft soil curing and shield tunnel reinforcement are achieved.

CN119822725APending Publication Date: 2025-04-15CHINA RAILWAY TUNNEL GROUP CO LTD +4
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510004504.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing soft soil curing agent and shield tunnel synchronous grouting materials have insufficient performance, including problems such as low early strength, long curing time, low strength, consumption of a large amount of sand resources, large carbon emissions, slurry water secretion, slow condensation time and weak reinforcement ability.

Method used

A composition is provided, including cement, red mud, calcium sulfate waste residue powder and water, preferably also includes a flocculant, a retarder, a water reducer and a gas induction agent. Through synergistic action, the composition can be cured to form high-quality concrete, improve salt resistance, corrosion resistance and waterproof performance, and improve flocculation ability and post-curing strength.

Benefits of technology

The composition has high early curing strength, good fluidity, micro-expansion characteristics after curing, good flocculation ability and high curing strength, which can effectively suppress disturbances of the soft base layer, prevent volume shrinkage and float up of the tube sheet, and has good anti-seepage pressure and salt corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005226464100000071
    Figure BDA0005226464100000071
  • Figure BDA0005226464100000081
    Figure BDA0005226464100000081
  • Figure BDA0005226464100000091
    Figure BDA0005226464100000091
Patent Text Reader

Abstract

The invention provides a composition and application thereof. The composition comprises cement, red mud, calcium sulfate waste residue powder and water, and preferably further comprises an additive consisting of a flocculating agent, a retarder, a water reducing agent and an air entraining agent. The composition provided by the invention can be applied to soft soil solidification or shield tunnel synchronous grouting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of a soft soil solidifying agent and a synchronous grouting material for a shield tunnel, and in particular relates to a composition and an application thereof. Background Art

[0002] Poor soil quality, low permeability, and low rheology make it very difficult to drain and consolidate soft soil foundations, which seriously affects the strength of the foundation. In addition, once this type of foundation soil layer is disturbed, it will deform and its strength will be significantly reduced, which makes the soil very prone to lateral slippage and settlement. The reinforcement of soft soil foundations is an indispensable process to ensure the safety and durability of structural engineering. At present, the most commonly used curing materials in soft soil reinforcement are mainly inorganic compounds, such as cement, lime, fly ash or industrial slag. This type of curing agent mainly generates gel-like substances through the hydration of inorganic materials, and forms a spatially stable network structure between soil particles to increase the stability of the soil. It has the advantages of low cost and good strength stability, but it also has the disadvantages of low early strength, long curing time in silt with high organic matter content, and low strength. Shield tunnel synchronous grouting is an underground tunnel construction technology that combines shield excavation and grouting. Shield tunnel synchronous grouting material is a material used to fill the gap between the excavated soil and the segment ring during tunnel shield construction to ensure the early stability of the segment lining, stabilize the segment and prevent floating. It also plays a role in supporting the stratum, reducing stratum subsidence and ensuring environmental safety. The shield tunnel synchronous grouting materials in the existing technology not only consume a large amount of sand resources, but also have the following problems during use: most of them use cement above grade 42.5, which has a large carbon emission; after being injected into the shield segment, due to the grouting pressure and the large amount of sand contained, the slurry is prone to bleeding during use; the setting time is slow and the slurry stability is poor; the cement particles are large in diameter and are restricted at small cracks, resulting in weak reinforcement between the segment and the original soil, and it is more likely to have problems such as water seepage and insufficient support in the later stage. Therefore, it is urgent to develop a new type of material suitable for soft soil solidification and shield tunnel synchronous grouting. Summary of the invention

[0003] One of the present inventions provides a composition comprising cement, red mud, calcium sulfate waste powder and water.

[0004] According to a specific embodiment of the present invention, the SO3 2- The content of is not higher than 3.5wt%, and the content of CaO is not lower than 38wt%;

[0005] Preferably, the fineness of the calcium sulfate waste slag powder is 150 to 200 meshes.

[0006] In the present invention, calcium sulfate waste residue powder refers to industrial waste residue generated in the gypsum production process, which still contains a large amount of calcium oxide, aluminum oxide, silicon dioxide, aluminum oxide and sulfur oxide.

[0007] According to a specific embodiment of the present invention, the composition further comprises an additive.

[0008] According to a specific embodiment of the present invention, the mass of the composition is calculated as 100%, and the composition includes 10 to 35 wt% of cement, 10 to 50 wt% of red mud, 3 to 20 wt% of calcium sulfate waste powder, 3 wt% of admixture and the balance of water;

[0009] Preferably, taking the mass of the composition as 100%, the composition comprises 10 to 35 wt% of cement, 20 to 50 wt% of red mud, 15 to 20 wt% of calcium sulfate waste slag powder, 3 wt% of admixture and the balance of water;

[0010] Further preferably, taking the mass of the composition as 100%, the composition comprises 30 to 35 wt % of cement, 20 to 30 wt % of red mud, 15 to 20 wt % of calcium sulfate waste powder, 3 wt % of admixture and the balance of water.

[0011] According to a preferred embodiment of the present invention, taking the mass of the composition as 100%, the composition includes 25 wt% of cement, 35 wt% of red mud, 15 wt% of calcium sulfate waste powder, 3 wt% of admixture and 22 wt% of water.

[0012] According to a specific embodiment of the present invention, the content of Al2O3 in the red mud is not less than 19wt%, and the content of Fe2O3 is not less than 36wt%;

[0013] Preferably, the fineness of the red mud is 200 to 300 meshes.

[0014] According to a specific embodiment of the present invention, the admixture includes a flocculant, a retarder, a water reducing agent and an air entraining agent.

[0015] According to a specific embodiment of the present invention, the mass of the admixture is calculated as 100%, and the admixture includes 23.3 to 33.4 wt% of flocculant, 10 to 33.4 wt% of retarder, 26.6 to 50 wt% of water reducer and 6.7 wt% of air entraining agent;

[0016] Preferably, taking the mass of the admixture as 100%, the admixture includes 23.3 to 33.4 wt % of flocculant, 20 to 33.4 wt % of retarder, 26.6 to 50 wt % of water reducer and 6.7 wt % of air entraining agent.

[0017] According to a specific embodiment of the present invention, the flocculant is a mixture of polyaluminium chloride and sodium hydroxypropyl cellulose; and / or

[0018] The retarder is a mixture of sodium gluconate and polyacrylamide; and / or

[0019] The water reducer is a polycarboxylate water reducer; and / or

[0020] The air entraining agent is a sodium rosin acid air entraining agent.

[0021] According to a preferred embodiment of the present invention, the weight average molecular weight of the hydroxypropyl cellulose sodium is 16 million;

[0022] and / or

[0023] The weight average molecular weight of the polyacrylamide is 14 million.

[0024] According to a specific embodiment of the present invention, the mass ratio of polyaluminium chloride to sodium hydroxypropyl cellulose is 1:1; and / or

[0025] The mass ratio of the sodium gluconate to the polyacrylamide is 27:53.

[0026] According to a specific embodiment of the present invention, the composition is prepared by the following method:

[0027] Mixing the cement, red mud, calcium sulfate waste residue powder and water to obtain the composition;

[0028] Preferably, the cement, red mud, calcium sulfate waste slag powder, admixture and water are mixed to obtain the composition;

[0029] Preferably, the mixing is performed by stirring; and / or

[0030] The stirring time is not less than 2 minutes.

[0031] The composition of the invention is used in soft soil solidification or synchronous grouting of shield tunnels.

[0032] Beneficial effects of the present invention:

[0033] In view of the problem that the performance of soft soil solidifying agents and synchronous grouting materials for shield tunnels in the prior art is not ideal, the present invention provides a composition and its application, wherein the composition includes cement, red mud, calcium sulfate waste slag powder and water, and preferably also includes an admixture consisting of a flocculant, a retarder, a water reducer and an air entraining agent. Among them, the synergy between cement, red mud and calcium sulfate waste slag powder is conducive to promoting the formation of high-quality concrete after the composition is solidified, improving the salt resistance, corrosion resistance and waterproof properties of cement, and can also neutralize the humus in the sludge and the calcification properties of secondary proteins; combined with the admixture, the composition has excellent flocculation ability and higher strength after solidification. Based on the above formula design, the composition has the following advantages compared with the prior art:

[0034] (1) The composition has good fluidity, micro-expansion characteristics after curing, and high early curing strength: the initial fluidity is between 410 and 460 mm, the 4h fluidity is between 200 and 235 mm, the 1d strength can reach 15 to 18 MPa, the 7d strength can reach 18.5 to 37 MPa, the 28d strength can reach 26 to 43 MPa, and the 28d expansion rate can reach 0.06 to 0.08%; it has good fluidity during grouting and is not easy to block the pipe; the early curing strength is high, which can effectively suppress the disturbance of the soft base layer; when used for synchronous grouting of shield tunnels, it can effectively prevent volume shrinkage and floating of pipe segments;

[0035] (2) The composition has good compatibility with silt and is easy to mix evenly, thus avoiding pile breakage when used for soft soil solidification;

[0036] (3) The composition has a 28-day anti-seepage pressure of 0.7 to 0.9 MPa, good water-stopping effect, high compressive strength, and strong pourability;

[0037] (4) The composition has good salt resistance and corrosion resistance. The maximum force maintenance rate of the test pieces prepared by adding medium sand to the composition after being immersed in salt water for 3d, 7d, and 28d can reach more than 63%, and the average compressive strength can reach more than 65% compared with the same age of standard curing.

[0038] (5) The composition uses a large proportion of red mud and calcium sulfate waste powder, both of which are solid wastes with low prices, which greatly saves material costs, is conducive to improving engineering benefits, and also solves the problem of solid waste disposal. DETAILED DESCRIPTION

[0039] The present invention will be further described below in conjunction with examples, but the examples of the present invention are only exemplary descriptions, and the implementation methods do not constitute limitations of the present invention under any circumstances.

[0040] The various raw material information in the following examples and comparative examples are as follows:

[0041] Sodium rosin acid air-entraining agent: purchased from Shaoxing Shangyu Yuanzheng Building Materials Co., Ltd.;

[0042] Calcium sulfate waste powder: SO3 2- The content of is not higher than 3.5wt%, the content of CaO is not lower than 38wt%, the fineness is 150 to 200 mesh, purchased from Jiangmen Zhongsenman Environmental Protection Building Materials Co., Ltd.;

[0043] Calcium sulfate: fineness is 150 to 200 mesh;

[0044] Desulfurized calcium sulfate: fineness is 150 to 200 mesh;

[0045] Calcium carbonate: fineness is 150 to 200 mesh;

[0046] Polyaluminium chloride: specifically powder-spraying polyaluminium chloride, purchased from Gongyi Maoquan Purification Materials Co., Ltd.;

[0047] Polycarboxylate water reducer: purchased from Foshan Xinqi Tuoda New Materials Group Co., Ltd.

[0048] Red mud: Al2O3 content not less than 19wt%, Fe2O3 content not less than 36wt%, fineness of 200 to 300 mesh, purchased from Guangxi Pingguo Aluminum Co., Ltd.;

[0049] Cement: Portland cement;

[0050] Hydroxypropyl cellulose sodium: weight average molecular weight is 16 million;

[0051] Polyacrylamide: The weight average molecular weight is 14 million.

[0052] Example 1

[0053] The composition 1 provided in this embodiment comprises, by weight percentage, 25% cement, 35% red mud, 15% calcium sulfate waste residue powder, 1% flocculant (polyaluminium chloride and sodium hydroxypropyl cellulose with a weight average molecular weight of 16 million in a mass ratio of 1:1), 0.8% retarder (sodium gluconate and polyacrylamide with a weight average molecular weight of 14 million in a mass ratio of 27:53), 1% polycarboxylate water reducer, 0.2% sodium rosin acid air entraining agent, and 22% water;

[0054] Mix the above non-aqueous components evenly, add water and stir evenly for ≥3 minutes before use.

[0055] Example 2

[0056] The composition 2 provided in this embodiment comprises, by weight percentage, 20% cement, 40% red mud, 15% calcium sulfate waste residue powder, 0.8% flocculant (polyaluminium chloride and sodium hydroxypropyl cellulose with a weight average molecular weight of 16 million in a mass ratio of 1:1), 0.8% retarder (sodium gluconate and polyacrylamide with a weight average molecular weight of 14 million in a mass ratio of 27:53), 1.2% polycarboxylate water reducer, 0.2% sodium rosin acid air entraining agent, and 22% water;

[0057] Mix the above non-aqueous components evenly, add water and stir evenly for ≥3 minutes before use.

[0058] Example 3

[0059] The composition 3 provided in this embodiment comprises, by weight percentage, 15% cement, 45% red mud, 15% calcium sulfate waste residue powder, 0.8% flocculant (polyaluminium chloride and sodium hydroxypropyl cellulose with a weight average molecular weight of 16 million in a mass ratio of 1:1), 0.6% retarder (sodium gluconate and polyacrylamide with a weight average molecular weight of 14 million in a mass ratio of 27:53), 1.4% polycarboxylate water reducer, 0.2% sodium rosin acid air entraining agent, and 22% water;

[0060] Mix the above non-aqueous components evenly, add water and stir evenly for ≥3 minutes before use.

[0061] Example 4

[0062] The composition 4 provided in this embodiment comprises, by weight percentage, 30% cement, 30% red mud, 15% calcium sulfate waste residue powder, 1% flocculant (polyaluminium chloride and sodium hydroxypropyl cellulose with a weight average molecular weight of 16 million in a mass ratio of 1:1), 1% retarder (sodium gluconate and polyacrylamide with a weight average molecular weight of 14 million in a mass ratio of 27:53), 0.8% polycarboxylate water reducer, 0.2% sodium rosin acid air entraining agent, and 22% water;

[0063] Mix the above non-aqueous components evenly, add water and stir evenly for ≥3 minutes before use.

[0064] Example 5

[0065] The composition 5 provided in this embodiment comprises, by weight percentage, 35% cement, 25% red mud, 15% calcium sulfate waste residue powder, 0.7% flocculant (polyaluminium chloride and sodium hydroxypropyl cellulose with a weight average molecular weight of 16 million in a mass ratio of 1:1), 0.6% retarder (sodium gluconate and polyacrylamide with a weight average molecular weight of 14 million in a mass ratio of 27:53), 1.5% polycarboxylate water reducer, 0.2% sodium rosin acid air entraining agent, and 22% water;

[0066] Mix the above non-aqueous components evenly, add water and stir evenly for ≥3 minutes before use.

[0067] Example 6

[0068] The composition 6 provided in this embodiment comprises, by weight percentage, 35% cement, 20% red mud, 20% calcium sulfate waste powder, 0.7% flocculant (polyaluminium chloride and sodium hydroxypropyl cellulose with a weight average molecular weight of 16 million in a mass ratio of 1:1), 0.6% retarder (sodium gluconate and polyacrylamide with a weight average molecular weight of 14 million in a mass ratio of 27:53), 1.5% polycarboxylate water reducer, 0.2% sodium rosin acid air entraining agent, and 22% water;

[0069] Mix the above non-aqueous components evenly, add water and stir evenly for ≥3 minutes before use.

[0070] Example 7

[0071] The composition 7 provided in this embodiment comprises, by weight percentage, 10% cement, 45% red mud, 20% calcium sulfate waste residue powder, 1% flocculant (polyaluminium chloride and sodium hydroxypropyl cellulose with a weight average molecular weight of 16 million in a mass ratio of 1:1), 0.3% retarder (sodium gluconate and polyacrylamide with a weight average molecular weight of 14 million in a mass ratio of 27:53), 1.5% polycarboxylate water reducer, 0.2% sodium rosin acid air entraining agent, and 22% water;

[0072] Mix the above non-aqueous components evenly, add water and stir evenly for ≥3 minutes before use.

[0073] Example 8

[0074] The composition 8 provided in this embodiment comprises, by weight percentage, 10% cement, 45% red mud, 20% calcium sulfate waste residue powder, 0.9% flocculant (polyaluminium chloride and sodium hydroxypropyl cellulose with a weight average molecular weight of 16 million in a mass ratio of 1:1), 0.4% retarder (sodium gluconate and polyacrylamide with a weight average molecular weight of 14 million in a mass ratio of 27:53), 1.5% polycarboxylate water reducer, 0.2% sodium rosin acid air entraining agent, and 22% water;

[0075] Mix the above non-aqueous components evenly, add water and stir evenly for ≥3 minutes before use.

[0076] Example 9

[0077] The composition 9 provided in this embodiment comprises, by weight percentage, 10% cement, 50% red mud, 15% calcium sulfate waste residue powder, 1% flocculant (polyaluminium chloride and sodium hydroxypropyl cellulose with a weight average molecular weight of 16 million in a mass ratio of 1:1), 0.3% retarder (sodium gluconate and polyacrylamide with a weight average molecular weight of 14 million in a mass ratio of 27:53), 1.5% polycarboxylate water reducer, 0.2% sodium rosin acid air entraining agent, and 22% water;

[0078] Mix the above non-aqueous components evenly, add water and stir evenly for ≥3 minutes before use.

[0079] Example 10

[0080] The composition 10 provided in this embodiment comprises, by weight percentage, 20% cement, 30% red mud, 3% calcium sulfate waste residue powder, 0.8% flocculant (polyaluminium chloride and sodium hydroxypropyl cellulose with a weight average molecular weight of 16 million in a mass ratio of 1:1), 0.6% retarder (sodium gluconate and polyacrylamide with a weight average molecular weight of 14 million in a mass ratio of 27:53), 1.4% polycarboxylate water reducer, 0.2% sodium rosin acid air entraining agent, and 44% water;

[0081] Mix the above non-aqueous components evenly, add water and stir evenly for ≥3 minutes before use.

[0082] Embodiment 11

[0083] The composition 11 provided in this embodiment comprises, by weight percentage, 20% cement, 40% red mud, 3% calcium sulfate waste powder, 0.8% flocculant (polyaluminium chloride and sodium hydroxypropyl cellulose with a weight average molecular weight of 16 million in a mass ratio of 1:1), 0.6% retarder (sodium gluconate and polyacrylamide with a weight average molecular weight of 14 million in a mass ratio of 27:53), 1.4% polycarboxylate water reducer, 0.2% sodium rosin acid air entraining agent, and 34% water;

[0084] Mix the above non-aqueous components evenly, add water and stir evenly for ≥3 minutes before use.

[0085] Comparative Example 1

[0086] The comparative composition 1 provided in this comparative example comprises, by weight percentage, 25% cement, 35% red mud, 15% calcium sulfate, 1% flocculant (polyaluminium chloride and sodium hydroxypropyl cellulose with a weight average molecular weight of 16 million in a mass ratio of 1:1), 0.8% retarder (sodium gluconate and polyacrylamide with a weight average molecular weight of 14 million in a mass ratio of 27:53), 1% polycarboxylate water reducer, 0.2% sodium rosin acid air entraining agent, and 22% water;

[0087] Mix the above non-aqueous components evenly, add water and stir evenly for ≥3 minutes before use.

[0088] Comparative Example 2

[0089] The comparative composition 2 provided in this comparative example comprises, by weight percentage, 25% cement, 35% red mud, 15% desulfurized calcium sulfate, 1% flocculant (polyaluminium chloride and sodium hydroxypropyl cellulose with a weight average molecular weight of 16 million in a mass ratio of 1:1), 0.8% retarder (sodium gluconate and polyacrylamide with a weight average molecular weight of 14 million in a mass ratio of 27:53), 1% polycarboxylate water reducer, 0.2% sodium rosin acid air entraining agent, and 22% water;

[0090] Mix the above non-aqueous components evenly, add water and stir evenly for ≥3 minutes before use.

[0091] Comparative Example 3

[0092] The comparative composition 3 provided in this comparative example comprises, by weight percentage, 25% cement, 35% red mud, 15% calcium carbonate, 1% flocculant (polyaluminium chloride and sodium hydroxypropyl cellulose with a weight average molecular weight of 16 million in a mass ratio of 1:1), 0.8% retarder (sodium gluconate and polyacrylamide with a weight average molecular weight of 14 million in a mass ratio of 27:53), 1% polycarboxylate water reducer, 0.2% sodium rosin acid air entraining agent, and 22% water;

[0093] Mix the above non-aqueous components evenly, add water and stir evenly for ≥3 minutes before use.

[0094] Comparative Example 4

[0095] The comparative composition 4 provided in this comparative example comprises, by weight percentage, 60% red mud, 15% calcium sulfate waste residue powder, 1% flocculant (polyaluminium chloride and sodium hydroxypropyl cellulose with a weight average molecular weight of 16 million in a mass ratio of 1:1), 0.8% retarder (sodium gluconate and polyacrylamide with a weight average molecular weight of 14 million in a mass ratio of 27:53), 1% polycarboxylate water reducer, 0.2% sodium rosin acid air entraining agent, and 22% water;

[0096] Mix the above non-aqueous components evenly, add water and stir evenly for ≥3 minutes before use.

[0097] Experimental evaluation

[0098] 1. Composition technical indicators

[0099] The following technical indicators were measured for the compositions 1 to 9 prepared in Examples 1 to 9 and Comparative Examples 1 to 4, and the comparative compositions 1 to 4, and the specific steps were as follows:

[0100] ⅰ Initial fluidity and 4h fluidity: Determined according to standard GB / T 2419-2005 "Mortar fluidity test method";

[0101] ⅱ1d strength, 7d strength, 28d strength: measured according to the standard JGJ / T 70-2009 "Standard for experimental methods of basic properties of building mortar";

[0102] ⅲ28d anti-seepage pressure: measured according to the standard JC / T 985-2017 "cement-based self-leveling mortar for floor";

[0103] ⅳ Expansion rate: measured in accordance with Appendix C of standard GB / T 50119-2013.

[0104] The results are shown in Table 1.

[0105] Table 1. Composition performance test results

[0106]

[0107]

[0108] It can be seen from Table 1 that the properties of the compositions prepared in Examples 1 to 9 are as follows: initial fluidity is 410 to 456 mm, 4h fluidity is 200 to 233 mm; 1d strength is 15.21 to 18.21 MPa, 7d strength is 18.56 to 37.23 MPa, 28d strength is 26.3 to 42.85 MPa; 28d impermeability pressure is 0.7 to 0.9 MPa; and expansion rate is 0.06 to 0.08%. It can be seen that the good fluidity of the composition provided by the present invention before solidification is conducive to on-site mixing construction. It does not contain aggregates and has fine slurry, and the filling of the gaps between the synchronous grouting segments of the shield tunnel can reach a saturated state; the micro-swelling property after solidification enables the composition to slightly expand without shrinkage after solidification, which can effectively prevent adverse phenomena such as floating, deformation and displacement of the segments; and the strength of the composition increases rapidly after 1 day during the experiment, and the strength requirement of 28 days can be reached after 3 days, which can meet the requirements of the solidification age of soft foundation silt; the synergy of cement, red mud and calcium sulfate waste slag powder makes the composition have ferroaluminate characteristics after solidification, achieves a higher 28d anti-seepage pressure, has good waterproof performance, and is also conducive to stabilizing the soil layer.

[0109] Compared with Example 1, in Comparative Example 1, the calcium sulfate waste powder is replaced with an equal mass of calcium sulfate. Although the strength of the composition provided in Comparative Example 1 after curing is slightly increased, its 28d anti-seepage pressure and expansion rate are slightly lower than those of Example 1, and the anti-seepage effect and expansion property are deteriorated; in Comparative Example 2, compared with Example 1, the calcium sulfate waste powder is replaced with an equal mass of desulfurized calcium sulfate. Although the strength of the composition provided in Comparative Example 2 after curing is slightly higher than that of Example 1 and the 28d anti-seepage pressure is equivalent to that of Example 1, its 4h flow strength is only 80mm, which is nearly 65% ​​lower than that of Example 1, and the fluidity is greatly reduced; in Comparative Example 3, compared with Example 1, the calcium sulfate waste powder is replaced with an equal mass of calcium carbonate, and the 1d strength, 7d strength and 28d strength are greatly reduced; in Comparative Example 4, cement is replaced with an equal mass of red mud. Although the fluidity is very high, the 1d, 7d and 28d strengths are seriously reduced, there is almost no strength, and the 28d anti-seepage pressure and expansion rate are also significantly reduced. The formula settings of Comparative Examples 1 to 4 all destroyed the synergy among cement, red mud and calcium sulfate waste slag powder, and different technical indicators all decreased significantly.

[0110] 2. Evaluation of compatibility between composition and sludge

[0111] The water in the formulas of compositions 1 to 9 provided in Examples 1 to 9 was replaced with a certain mass of sludge having a certain water content, so that the mass of water in the sludge was equal to the mass of water in the compositions provided in Examples 1 to 9, and formulas 1 to 9 were obtained in sequence, and then the following technical indicators were measured to evaluate the compatibility of the composition with the sludge:

[0112] A. Initial fluidity and 4h fluidity: Determined according to standard GB / T 2419-2005 "Mortar fluidity test method";

[0113] B.1d strength, 7d strength, 28d strength: measured according to the standard JGJ / T 70-2009 "Standard for basic performance test methods of building mortar";

[0114] C.28d anti-seepage pressure: measured according to the standard JC / T 985-2017 "cement-based self-leveling mortar for floor";

[0115] D. Expansion rate: measured in accordance with Appendix C of GB / T 50119-2013.

[0116] The formula for evaluating the compatibility of the composition with sludge is shown in Table 2, and the experimental data is shown in Table 3.

[0117] Table 2. Formula for evaluating compatibility of composition with sludge

[0118]

[0119] Table 3. Compatibility test results of the composition and sludge

[0120]

[0121] From the data in Table 3, it can be seen that the initial fluidity, 4h fluidity, 1d strength, 7d strength, 28d strength, 28d anti-seepage pressure and expansion rate of formulas 1 to 9 all meet the requirements of the standards based on which the indicators are measured, proving that the composition provided by the present invention has good compatibility with sludge with a water content of 40% to 80%. Among them, the composition prepared by Examples 4 to 6 corresponding to formulas 4 to 6 has the best compatibility with sludge with a water content of 55% to 65%, while maintaining a relatively high initial fluidity (450 to 540 mm) and 4h fluidity (370 to 430 mm), it has the highest 1d strength (3.98 to 5.85 MPa), 7d strength (11.69 to 14.14 MPa), 28d strength (15.2 to 18.21 MPa) and the highest 28d anti-seepage pressure (0.8 MPa) and expansion rate (0.7 to 0.8%).

[0122] 3. Evaluation of salt and corrosion resistance of the composition

[0123] a. Preparation of test pieces for salt and corrosion resistance test:

[0124] A certain proportion of medium sand was added to the compositions 10 and 11 prepared in Example 10 and Example 11, respectively. After being mixed evenly, the mixture was placed in a mold to prepare test pieces with a size of 70.7 mm×70.7 mm×70.7 mm. The formula of each test piece is shown in Table 4.

[0125] Table 4. Test pieces for salt and corrosion resistance test

[0126] Recipe Number Recipe Type Formula: cement: red mud: medium sand: calcium sulfate waste powder Recipe A Composition 10+ Medium Sand 1:1.5:3:0.15 Recipe B Composition 11+ Medium Sand 1:2:4:0.15

[0127] b. Determination of salt and corrosion resistance

[0128] The specimens obtained in step a are subjected to mortar compression tests under standard curing and salt water immersion conditions according to the provisions of standard JGJ / T 70-2009 "Standard for Test Methods for Basic Properties of Building Mortar", and the maximum force (or specimen failure load) and compressive strength at different ages are specifically measured, and the average strength is calculated;

[0129] The standard curing conditions are as follows: after the specimens are demoulded, the surface layer is covered with clean water and cured at room temperature for 3d, 7d, and 28d;

[0130] The conditions for brine immersion are as follows: after the specimen is demolded, the surface layer is covered with brine and immersed for 3d, 7d, and 28d at room temperature; the brine used is a NaCl aqueous solution, the mass of the brine is counted as 100%, of which the NaCl content is 5wt%; the experimental results are shown in Table 5.

[0131] Table 5. Test results of salt and corrosion resistance of specimens

[0132]

[0133]

[0134] According to the data in Table 5, (1) for the 3-day-old specimens: the maximum force maintenance rate of the salt water immersion treatment of Formula A relative to the standard curing treatment was 88.7% to 91.5%, and the average compressive strength maintenance rate was 89.9%; the maximum force maintenance rate of the salt water immersion treatment of Formula B relative to the standard curing treatment was 87.6% to 93%, and the average compressive strength maintenance rate was 91%. (2) For the 7-day-old specimens: the maximum force maintenance rate of the salt water immersion treatment of Formula A relative to the standard curing treatment was 72.2% to 75.2%, and the average compressive strength maintenance rate was 73.5%; the maximum force maintenance rate of the salt water immersion treatment of Formula B relative to the standard curing treatment was 80.1% to 91.3%, and the average compressive strength maintenance rate was 84%. (3) For the specimens at 28 days of age: the maximum force maintenance rate of the salt water immersion treatment of Formula A relative to the standard curing treatment is 63% to 69%, and the average compressive strength maintenance rate is 65.6%; the maximum force maintenance rate of the salt water immersion treatment of Formula B relative to the standard curing is 71.4% to 78.3%, and the average compressive strength maintenance rate is 74.1%. In summary, the maximum force maintenance rates of Formula A and Formula B at 3d, 7d, and 28d of salt water immersion are all above 63%, and the average compressive strength maintenance rates are all above 65%, indicating that Formula A and Formula B have good salt and corrosion resistance, that is, it proves that the composition provided by the present invention has good salt and corrosion resistance.

[0135] Although the present invention has been described with reference to specific embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention. In addition, the subject matter, spirit and scope of the present invention may be varied to accommodate specific situations, materials, material combinations and methods. All of these changes are included within the scope of the claims of the present invention.

Claims

1. A composition comprising cement, red mud, calcium sulfate waste slag powder and water.

2. The composition according to claim 1, characterized in that The calcium sulfate waste powder contains SO3 2- The content of is not higher than 3.5wt%, and the content of CaO is not lower than 38wt%; Preferably, the fineness of the calcium sulfate waste slag powder is 150 to 200 meshes.

3. The composition according to claim 1 or 2, characterized in that The composition also includes an admixture.

4. The composition according to claim 3, characterized in that Taking the mass of the composition as 100%, the composition includes 10 to 35 wt % of cement, 10 to 50 wt % of red mud, 3 to 20 wt % of calcium sulfate waste powder, 3 wt % of an admixture and the balance of water.

5. The composition according to any one of claims 1 to 4, characterized in that The content of Al2O3 in the red mud is not less than 19wt%, and the content of Fe2O3 is not less than 36wt%; Preferably, the fineness of the red mud is 200 to 300 meshes.

6. The composition according to claim 3 or 4, characterized in that The admixtures include flocculants, retarders, water reducers and air entraining agents.

7. The composition according to claim 6, characterized in that Taking the mass of the admixture as 100%, the admixture includes 23.3 to 33.4 wt % of flocculant, 10 to 33.4 wt % of retarder, 26.6 to 50 wt % of water reducer and 6.7 wt % of air entraining agent.

8. The composition according to claim 6 or 7, characterized in that The flocculant is a mixture of polyaluminium chloride and sodium hydroxypropyl cellulose; and / or The retarder is a mixture of sodium gluconate and polyacrylamide; and / or The water reducer is a polycarboxylate water reducer; and / or The air entraining agent is a sodium rosin acid air entraining agent.

9. The composition according to claim 8, characterized in that The mass ratio of the polyaluminium chloride to sodium hydroxypropyl cellulose is 1:1; and / or The mass ratio of the sodium gluconate to the polyacrylamide is 27:

53.

10. Use of the composition according to any one of claims 1 to 9 in soft soil consolidation or synchronous grouting of shield tunnels.